Development of GIDI-SNAKE Media Based on Powtoon Animation Video on the Material of Formulation and Establishment of Pancasila to Improve Learning Achievement - Solikah, Alik Ulfatus; Hady, Nuruddin; Sukriono, Didik (EDUTEC : Journal of Education And Technology, 2025)
The learning achievement of seventh-grade students at SMP Negeri 1 Tugu is still relatively low, particularly in the material of formulating and establishing Pancasila as the state ideology, which is approached textually. This issue is exacerbated by the minimal use of innovative learning media by teachers. This development research aims to develop a GIDI-SNAKE learning media product based on Powtoon animation videos to address the learning issues at SMP Negeri 1 Tugu, Trenggalek Regency, and to test the product based on its validity, practicality, and effectiveness. The research model used is the ADDIE model. The specifications of the developed product include a GIDI-SNAKE game board with game instruments consisting of question cards and information cards, each equipped with a barcode integrated with Powtoon animation videos. Since GIDI-SNAKE is a development of the traditional Snakes and Ladders game, it is also equipped with dice, pawns, and cue cards or guide cards. The data analysis used descriptive statistics with a paired sample t-test after being tested and confirmed as valid, reliable, and normal. The results of the study show that the developed media meets the levels of validity, practicality, and effectiveness. It meets the validity level with an average validation score of 3.84 from two media validators and 3.70 from the material validator. It meets the practicality level with a positive response from students, achieving a 94.7% approval rate. It meets the effectiveness level, as the results of the Paired sample t-test showed an average pre-test score of 41.29 and a post-test score of 85.23, with a significance value (sig) of 0.001 < 0.05, indicating a significant improvement in learning outcomes, thus confirming the media’s effectiveness.